Changing Pattern Of Prostitution: An Assessment Of Transnational Commercial Sex Work By Nigerian Women - Ibrahim, Bello; Mukhtar, Jamilu Ibrahim (European Scientific Journal, ESJ, 2016)
This paper is aimed at analyzing the changing pattern of prostitution. However, the definition of the act of prostitution has been metamorphosing for centuries from acceptable to illegal and then (in some jurisdictions) to criminal again, agitations by advocates have also necessitated the nomenclatural alteration from “prostitution” to “commercial sex work”. The paper examined how development in information and communication technology allows commercial sex workers to make connections with clients through internet and sell sex on this platform. Globalization processes has also changed the pattern of this business to a transnational activity. Although there are many willing transnational commercial sex workers, but organized criminal syndicates are using this development to traffic some women and children with the false promises of getting a lucrative from overseas but ultimately subject them to sex exploitation, child prostitution and sex labor. As is the plight of some Nigerian women in Italy and other European, Middle Eastern and Asian countries, many women from developing countries are recruited into this institution through human trafficking. As a result of commercial sex many women and girls suffer sexual violence, sex exploitation, sexual abuse and contract STDs. To curtail these problems, governments and transnational institutions are therefore urged to develop mechanisms that can tackle these problems by providing women with decent employment opportunities and increase surveillance across national borders.